Penyalahgunaan Data Pribadi Sebagai Bentuk Kejahatan Sempurna Dalam Perspektlf Hukum Siber - Fara Anindita Salsabila; Andi Aina IImih (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The misuse of personal data has become a highly relevant issue in the digital age, where cases of privacy violations are increasing sharply. Personal data such as contact information, transaction history, and online activities have become prime targets for cybercriminals to use for fraud, identity theft, and even political manipulation. These crimes often occur in various locations around the world, taking advantage of regulatory breaks and jurisdictional differences, making law enforcement difficult. To address this problem, a multi-dimensional approach is required. Stricter regulations, such as the General Data Protection Regulation (GDPR) in the European Union, are needed to protect personal data with strict sanctions for violations. In addition, international collaboration is essential as cybercrime often crosses national borders, requiring close cooperation between countries to track and apprehend perpetrators. Public awareness and education are also key components in reducing the risk of cybercrime. People should be encouraged to take proactive measures such as the use of strong passwords and two-step verification. Companies and service providers also need to take responsibility for customer data security by implementing strong protection measures and transparency in data management. In conclusion, the use of personal data as a form of perfect crime is a complex issue, requiring strict regulation, international collaboration, and awareness raising to create a safer digital environment.